Adolescent risk-taking and decision making: a qualitative investigation of a virtual reality experience of gangs and violence - Bilello, Delfina; Swancott, Lucy J.; Kloess, Juliane A.; Burnett Heyes, Stephanie (Frontiers in Virtual Reality, 2023)
Gang involvement poses serious risks to young people, including antisocial and criminal behaviour, sexual and criminal exploitation, and mental health problems. There is a need for research-informed development of preventive interventions. To this end, we conducted a qualitative study of young people’s responses to an educational virtual reality (VR) experience of an encounter with a gang, in order to address the overarching research question: What are young peoples’ experiences of a VR encounter with a gang, in terms of decisions, emotions and consequences? Young people (N=24 aged 13-15, 11 female, 13 male) underwent the VR experience before participating in semi-structured focus group discussions. Questions focused on virtual decision-making (motivations, thoughts, feelings, consequences) and user experiences of taking part. Results analysed using Thematic Analysis show how participants’ perceptions of the gang, themselves, and the context influenced virtual decisions. Social pressure from the gang competed with participants’ wish to stand by their morals and establish individual identity. The VR setting, through its escalating events and plausible characters, created an ‘illusion of reality’ and sense of authentic decisions and emotions, yielding insights for real-life in a safe, virtual environment. Findings shed light on processes influencing adolescent decision-making in a virtual context of risk-taking, peer pressure and contact with a gang. Particularly, they highlight the potential for using VR in interventions with young people, given its engaging and realistic nature.